2015
DOI: 10.3748/wjg.v21.i47.13386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraperitoneal local anesthetic on pain characteristics after laparoscopic cholecystectomy

Abstract: Intraperitoneal local anesthetic as an analgesic adjuvant in patients undergoing laparoscopic cholecystectomy exhibited beneficial effects on postoperative abdominal, visceral, and shoulder pain in a resting state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 51 publications
0
32
0
5
Order By: Relevance
“…[23] Laparoskopik kolesistektomilerde peritrokal lokal anestezik infiltrasyonu, [17,18] peritoneal boşluğa loakl anestezik uygulaması, [24] subdiafragmatık alana lokal anestezik, [19,25] peritrokal ve peritoneal alana birlikte lokal anestezik uygulaması [26,27] ile ağrının azaltılmasını amaçlayan çeşitli çalışmalar gerçekleştirilmesine rağmen sonuçlar çelişkilidir. Choi ve ark., [28] bir meta-analiz araştırmasında; laparoskopik kolesistektomilerde İPLA uygulamasının postoperatif dönemde istirahatteki viseral abdominal ve omuz ağrısını azalttığını ancak istirahatteki parietal ağrıyı ve hareket halindeki abdominal ağrıyı azaltmadığını tesbit etmişlerdir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…[23] Laparoskopik kolesistektomilerde peritrokal lokal anestezik infiltrasyonu, [17,18] peritoneal boşluğa loakl anestezik uygulaması, [24] subdiafragmatık alana lokal anestezik, [19,25] peritrokal ve peritoneal alana birlikte lokal anestezik uygulaması [26,27] ile ağrının azaltılmasını amaçlayan çeşitli çalışmalar gerçekleştirilmesine rağmen sonuçlar çelişkilidir. Choi ve ark., [28] bir meta-analiz araştırmasında; laparoskopik kolesistektomilerde İPLA uygulamasının postoperatif dönemde istirahatteki viseral abdominal ve omuz ağrısını azalttığını ancak istirahatteki parietal ağrıyı ve hareket halindeki abdominal ağrıyı azaltmadığını tesbit etmişlerdir.…”
Section: Discussionunclassified
“…meta-analiz çalışmalarında yara infiltrasyonu ile parietal ağrının azalmadığını saptamışlardır. [28] Das ve ark., [32] İPLA infiltrasyonunun laparoskopik kolesistektomilerde erken postoperatif dönemde ağrı skorlarını anlamlı şekilde azalttığı bildirilmiştir. Bizim çalışmamızda da erken dönemdeki ağrı skorları İPLA uygulananlarda daha düşük idi.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several manifestations of laparoscopic cholecystectomy related postoperative pain were described: Visceral pain related to tissue injury and stretching of nerve endings, parietal pain related to port sites and referral shoulder pain related to stretching and irritation of the diaphragm by carbon dioxide gas [8, 9]. Ways to minimize postoperative pain might thus be a restricted number and size of ports [10] or the avoidance of residual pneumoperitoneum at the end of the procedure [9].…”
Section: Discussionmentioning
confidence: 99%
“…15 Choi GJ et al have also concluded that intraperitoneal local anesthetic as an analgesic adjuvant in patients undergoing laparoscopic cholecystectomy exhibited beneficial effects on postoperative abdominal, visceral, and shoulder pain. 16 …”
mentioning
confidence: 99%